Drugs, cancer and end-of-life care: A case study of pharmaceuticalization? - Davis, Courtney (Soc Sci Med, 2015)
There is evidence from some countries of a trend towards increasingly aggressive pharmacological treatment of patients with advanced, incurable cancer. To what extent should this be understood as a progressive development in which technological innovations address previously unmet needs, or is a significant amount of this expansion explained by futile or even harmful treatment? In this article it is argued that while some of this growth may be consistent with a progressive account of medicines consumption, part of the expansion is constituted by the inappropriate and overly aggressive use of drugs. Such use is often explained in terms of individual patient consumerism and/or factors to do with physician behaviour. Whilst acknowledging the role of physicians and patients' expectations, this paper, drawing on empirical research conducted in the US, the EU and the UK, examines the extent to which upstream factors shape expectations and drive pharmaceuticalisation, and explores the value of this concept as an analytical tool.